Dopant‐free passivating contacts for crystalline silicon solar cells: Progress and prospects - Yanhao Wang; Shan‐Ting Zhang; Le Li; Xinbo Yang; Linfeng Lu; Dongdong Li (EcoMat, 2023)
Abstract The evolution of the contact scheme has driven the technology revolution of crystalline silicon (c‐Si) solar cells. The state‐of‐the‐art high‐efficiency c‐Si solar cells such as silicon heterojunction (SHJ) and tunnel oxide passivated contact (TOPCon) solar cells are featured with passivating contacts based on doped Si thin films, which induce parasitic optical absorption loss and require capital‐intensive deposition processes involving flammable and toxic gasses. A promising solution to tackle this problem is to employ dopant‐free passivating contact, involving the use of transparent and cost‐effective wide band gap materials. In this review, we first introduce the dopant‐free passivating contact, from carrier transport mechanisms, material classification to evaluation methods. Then we focus on the advances in different strategies to improve cell performance, including material property optimization, structural and interfacial engineering, as well as various post‐treatments. At the end, the challenge and perspective of dopant‐free passivating contact c‐Si solar cells are discussed.